Characterization of radiation-induced effects in amorphous arsenic sulfides by positron annihilation lifetime spectroscopy. Issue 9 (27th January 2015) - Shpotyuk, Mykhaylo; Ingram, Adam; Shpotyuk, Oleh
Abstract: Abstract : Positron annihilation lifetime spectroscopy is used to study the structural changes in amorphous arsenic sulfides of a binary As–S system induced by high-energy γ-radiation of 60 Co source. It is demonstrated that radiation-induced effects in positron trapping modes of the studied glasses are in strict correlation with shift of their fundamental optical absorption edge. The γ-induced physical aging is shown to be dominated in the rejuvenated S-rich glasses, thermally induced physical aging accompanies annealing of the rejuvenated g-As x S100− x, while coordination topological defects are character for near-stoichiometric glasses (both annealed and rejuvenated). The competitive processes of free-volume void evolutions such as agglomeration–fragmentation, expansion–contraction, and charging–discharging are considered as possible stages of radiation- and thermally induced structural transformations. The meaningful model for γ-irradiation and relaxation-driven evolution in the void structure of As–S glasses is proposed. The free-volume evolution in g-As x S100− x associated with thermally and γ-induced physical aging is shown to be consistent with a void fragmentation process, while the formation of γ-induced coordination topological defects leads mainly to void charging.